Prevalence and predictors of sleep apnea in patients with stable coronary artery disease: a cross-sectional study - Alonderis A; Varoneckas G; Raskauskiene N; Brozaitiene J (Dove Medical Press, 2017)
Audrius Alonderis,1 Giedrius Varoneckas,1 Nijole Raskauskiene,2 Julija Brozaitiene1 1Laboratory of Clinical Physiology and Rehabilitation, Behavioral Medicine Institute, Lithuanian University of Health Sciences, Palanga, Lithuania; 2Laboratory of Psychosomatic Research, Behavioral Medicine Institute, Lithuanian University of Health Sciences, Palanga, Lithuania Background: Sleep apnea (SA) is increasingly recognized as being important in the prognosis of patients with coronary artery disease (CAD); however, symptoms of SA are not easily identified, and as many as 80% of sufferers remain undiagnosed. Aim: This cross-sectional study investigated the prevalence and predictors of SA that may help to increase the awareness and diagnosis of SA in stable CAD patients. Materials and methods: Polysomnography was performed in 772 medically stable CAD patients with untreated SA recruited from the Clinic of Cardiovascular Rehabilitation. Patients were predominantly male (76%), median age was 58 years (32–81). All subjects completed the Epworth sleepiness scale (ESS). The frequency of all apneas and hypopneas associated with 3% oxygen desaturation is referred to as the apnea–hypopnea index (AHI). Mild-to-severe SA was defined as AHI ≥5/h, moderate-to-severe SA as AHI ≥15/h. Results: AHI was within a range of values that was considered normal or only mildly elevated. The median AHI was 3.4 (interquartile range [IQR 1–9]), and 39% of patients had unrecognized mild-to-severe SA (moderate-to-severe in 14%), which was not higher than other known risk indicators for CAD such as hypertension and obesity (83% and 47%, respectively). These patients did not show sleepiness and the risk-related cut-off score for excessive daily sleepiness was lower than the official for ESS. Conclusion: Hypertension, age, male gender, obesity, ESS ≥6, and left ventricular ejection fraction ≤45% were the best predictors of mild-to-severe SA. While, male gender, age 50–70 years and, mainly, the presence of obesity but not hypertension were clinical predictors for moderate-to-severe SA. In addition, association between mild-to-severe SA and obesity was not evident in women. SA is prevalent comorbidity in the stable CAD patients, especially in its asymptomatic mild form. We suggest that SA should be considered in the secondary prevention protocols for CAD. Keywords: apnea–hypopnea index, AHI, age, CAD, gender differences, sleep apnea